2017
DOI: 10.1186/s12958-017-0309-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of microRNAs in embryo implantation

Abstract: Failure of embryo implantation is a major limiting factor in early pregnancy and assisted reproduction. Determinants of implantation include the embryo viability, the endometrial receptivity, and embryo-maternal interactions. Multiple molecules are involved in the regulation of implantation, but their specific regulatory mechanisms remain unclear. MicroRNA (miRNA), functioning as the transcriptional regulator of gene expression, has been widely reported to be involved in embryo implantation. Recent studies rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
111
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(120 citation statements)
references
References 101 publications
(123 reference statements)
0
111
0
Order By: Relevance
“…miRNAs have been demonstrated to be involved in embryo implantation through regulating target genes (24,25). miRNAs control the expression of target genes, and 60% of them are predicted to be regulators of protein-encoding genes in humans (26).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs have been demonstrated to be involved in embryo implantation through regulating target genes (24,25). miRNAs control the expression of target genes, and 60% of them are predicted to be regulators of protein-encoding genes in humans (26).…”
Section: Discussionmentioning
confidence: 99%
“…Despite numerous advancements in assisted reproductive technology (ART), the efficiency of pregnancy has not greatly improved. Assessments of embryo quality remain an important challenge in successful pregnancy outcomes …”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that, from the first trimester, small EVs, acting through their miRNAs, modulate communications between embryonic cells of the blastocyst and endometrial cells, promoting the receptivity of one and the adhesion of the other. In detail, it has been demonstrated that miRNA210 could be used as an index of a good implant, therefore possibly predicting an eventual receptivity failure [86].…”
Section: Receptivity Failurementioning
confidence: 99%